Effectiveness of the Application of Fines in Traffic Violations in the Jurisdiction of Dumai Police Resort - Heriawan, Doni; Abidin Pakpahan, Zainal; Siahaan, Nimrot (International Journal Labs, 2024)
Traffic violations are a problem that continues to be faced by the Dumai Police jurisdiction. Applying criminal fines as sanctions for these violations is expected to reduce the number of violations and improve road safety. The purpose of this study is to explain the effectiveness of the application of criminal fines for traffic violations in the jurisdiction of the Dumai Police Station and to explain the factors that influence the occurrence of traffic violations in the jurisdiction of the Dumai Police Station. The method used in this research is a sociological juridical approach (sociolegal). The results showed that applying criminal fines for traffic violations at Dumai Police Station is still adequate. This can be seen from the number of offenders required to pay fines by the rules in Law Number 22 of 2009 concerning Road Traffic and Transportation. However, even though fines have been applied, they have yet to have a significant deterrent effect on violators. Violators often consider fines a redeemable punishment, making it possible for them to repeat the same offence in the future. Therefore, imprisonment should be considered in addition to fines to provide a more substantial deterrent effect. Factors that influence the occurrence of traffic violations in the jurisdiction of Dumai Police include human factors, vehicle factors, and road condition factors. This research implies the need to evaluate and review the policy of applying criminal fines for traffic violations. A combination of fines and imprisonment can increase the deterrent effect and reduce the number of traffic violations in the jurisdiction of Dumai District Police.